Засоби демонстрації мультимедійних продуктів - Григор’єв, О. В.; Вовк, О. В. (ТОВ «Видавництво Ліра-К», 2025)
The main hardware for demonstrating multimedia products is considered. Their main characteristics are indicated, which must be taken into account when choosing for demonstrating created multimedia products.
Keywords: мультимедіа; демонстрація